A Selective and Sensitive Gas Chromatography-Tandem Mass Spectrometry Method for Quantitation of Synthetic Musks in Human Serum. (10th April 2020) - Katuri, Guru Prasad; Fan, Xinghua; Siddique, Shabana; Kubwabo, Cariton; Kosarac, Ivana; Harris, Shelley A; Foster, Warren G
Abstract: Background: Synthetic musk compounds are widely used as fragrances in many consumer products; however, information on human exposure and health effects is limited. Also, analytical methods for their quantification in biological matrices are limited. Objective: In this study, an integrated method was developed and validated for the analysis of selected synthetic musk compounds in human serum. Method: The method is based on liquid-liquid extraction (LLE), sample clean-up by solid-phase extraction (SPE), and separation and detection by gas chromatography coupled with tandem mass spectrometry (GC-MS/MS). Results: The method demonstrated good recoveries (86–105%) and high sensitivity, with low method detection limits (MDLs) ranging from 0.04 to 0.17 µg/L. The method was applied to the analysis of 10 synthetic musk compounds in 40 serum samples collected from Canadian women aged 20–44 years (20 individual samples collected in 2014 and 20 pooled samples collected in 2006). The most commonly detected compound was Galaxolide (HHCB), with median concentrations of 0.59 µg/L in samples collected in 2006, and 0.34 µg/L for samples collected in 2014. Musk ketone (MK) was not detected in any of the samples collected in 2006, but was detected in 60% of the samples collected in 2014 with a median concentration of 0.29 µg/L. Tonalide (AHTN) was detected in only one sample above its MDL (0.12 µg/L). Conclusions: This is the first study in Canada to report levels of synthetic musks in human. The data generated from this study has been used in risk screening assessment by Environment and Climate Change Canada and Health Canada.